2007
DOI: 10.1080/09670260701476087
|View full text |Cite
|
Sign up to set email alerts
|

Heterothallic auxosporulation, incunabula and perizonium inPinnularia(Bacillariophyceae)

Abstract: The cytology and life cycle of Pinnularia cf. gibba was examined in nine clones from three Scottish localities. This freshwater epipelic diatom is heterothallic and produces two isogametes per gametangium in type IC auxosporulation (Geitler's classification [1973]). The zygote undergoes a highly unusual metamorphosis before beginning expansion, becoming shortly linear-lanceolate; this is accompanied by formation of a complete covering of thin, oxidation-resistant strips and scale-like structures (at the poles)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 43 publications
0
44
0
1
Order By: Relevance
“…This sequence of events is similar to what has been reported for some other diatoms, including the benthic raphid diatoms Seminavis robusta (Chepurnov et al, 2002) and Pinnularia cf. gibba (Poulíčková et al, 2007), but different patterns have been reported within raphid diatoms (reviewed by Chepurnov et al, 2004). As an example, only one uninucleate gamete is formed in each gametangium of the benthic freshwater genus Sellaphora (Mann, 1989), while two uninucleate gametes are produced in each gametangium of Pseudo-nitzschia pungens (Chepurnov et al, 2005).…”
Section: Transition From the Vegetative To The Sexual Phase And Formamentioning
confidence: 99%
“…This sequence of events is similar to what has been reported for some other diatoms, including the benthic raphid diatoms Seminavis robusta (Chepurnov et al, 2002) and Pinnularia cf. gibba (Poulíčková et al, 2007), but different patterns have been reported within raphid diatoms (reviewed by Chepurnov et al, 2004). As an example, only one uninucleate gamete is formed in each gametangium of the benthic freshwater genus Sellaphora (Mann, 1989), while two uninucleate gametes are produced in each gametangium of Pseudo-nitzschia pungens (Chepurnov et al, 2005).…”
Section: Transition From the Vegetative To The Sexual Phase And Formamentioning
confidence: 99%
“…Thus, the polarity shown in the development of the incunabula, from the poles inwards, is opposite to that of the transverse perizonium. No polarity was detected in the other incunabula studied recently by SEM, in Nitzschia fonticola (trobajo et al 2006) and Pinnularia (Poulíčková et al 2007), though it would be more difficult to detect the direction of overlaps in the systems of narrow strips found in these diatoms. Mann (1984) considered that, because the caps of Neidium bore the same spatial and temporal relationship to the auxospore and perizonium as the scales of Rhabdonema, the caps were probably "homologous with the scales of Rhabdonema and centric auxospores", but that "electron microscopy will be necessary to determine to what extent the homology is reflected in structure as well as position."…”
Section: Discussionmentioning
confidence: 95%
“…Grun. (trobajo et al 2006) and Pinnularia (Poulíčková et al 2007) suggests that Rhoicosphenia and Caloneis should be reinvestigated. kaczMarSka et al (2000) showed the presence of small circular scales during auxosporulation in Pseudonitzschia multiseries (haSlE) Hasle and claimed that they were present before plasmogamy on the passive (female) gamete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations